Elaboration and validation of method of quantitative determination of diclofenac in polymeric microspheres - Tam Nguen Tkhi Tkhan; S. A. Kedik; A. E. Baldaev; S. V. Belyakov; V. V. Suslov; E. V. Vorfolomeeva; E. A. Petrova; S. G. Beksaev (Тонкие химические технологии)
This article describes a new method of determining concentration of active ingredient in diclofenac-loaded polymer microspheres by using HPLC analysis. Proposed method showed better repeatability than more commonly used UV-Vis spectrometry. Isocratic liquid chromatograph with Luna C18 (2) Phenomenex column and UV detector (254 nm) was employed. Various parameters, such as specificity, repeatability, limit of quantification and stability, were measured to validate the method. Chromatogram showed only diclofenac-related peaks, which means specificity was adequate. Recovery was determined using 5 standard diclofenac solutions with known concentration. Repeatability and reproducibility were calculated based on data from two series of microspheres. LOQ was found using standard curve. Stability was observed during 30 days since sample preparation. Based on these results, suggested method successfully passed the validation process and can be used for quality control of diclofenac-loaded microspheres.